Emerging Roles of Extracellular Vesicles in the Central Nervous System: Physiology, Pathology, and Therapeutic Perspectives - Gassama, Yadaly; Favereaux, Alexandre (Frontiers in Cellular Neuroscience, 2021)
Extracellular vesicles or EVs are secreted by most, if not all, eukaryote cell types and recaptured by neighboring or distant cells. Their cargo, composed of a vast diversity of proteins, lipids and nucleic acids, supports the EVs’ inter-cellular communication. The role of EVs in many cellular processes is now well-documented both in physiological and pathological conditions. In this review, we focus on the role of EVs in the central nervous system, in physiological as well as pathological conditions such as neurodegenerative diseases or brain cancers. We also discuss the future of EVs in clinical research, in particular their value as biomarkers as well as innovative therapeutic agents. While an increasing number of studies reveal EV research as a promising field, progress in the standardization of protocols and innovation in analysis as well as in research tools is needed to make a breakthrough in our understanding of their impact in the pathophysiology of the brain.